2019
DOI: 10.1186/s13018-019-1286-7
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative 3D imaging leads to substantial revision rate in management of tibial plateau fractures in 559 cases

Abstract: Introduction The aim of this study was to evaluate the intraoperative revision rate and reasons for revision following 3D imaging in the management of dislocated articular tibial plateau fractures based on a large patient sample. Methods This retrospective cohort study included all patients who underwent open reduction and internal fixation due type B or C tibial plateau fracture according to the AO/OTA classification between August 2001 and December 2017 using intraope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 21 publications
0
36
0
3
Order By: Relevance
“…Intraoperative 3D scan has been comparable in most of the cases to postoperative CT scan in terms of quality of fracture reduction, with the added ability to intraoperatively evaluate implant positioning [27], joint width and geometry as well as small dislocated fragments in the intercondylar area. Beisemann et al published an intraoperative revision rate of up to 32.4% with intraoperative 3D imaging after initial satisfying reduction under fluoroscopic control [28]. They also detected relevant intraarticular fragments, which would have remained undetected in conventional fluoroscopy [28].…”
Section: Intraoperative 3d-imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraoperative 3D scan has been comparable in most of the cases to postoperative CT scan in terms of quality of fracture reduction, with the added ability to intraoperatively evaluate implant positioning [27], joint width and geometry as well as small dislocated fragments in the intercondylar area. Beisemann et al published an intraoperative revision rate of up to 32.4% with intraoperative 3D imaging after initial satisfying reduction under fluoroscopic control [28]. They also detected relevant intraarticular fragments, which would have remained undetected in conventional fluoroscopy [28].…”
Section: Intraoperative 3d-imagingmentioning
confidence: 99%
“…Beisemann et al published an intraoperative revision rate of up to 32.4% with intraoperative 3D imaging after initial satisfying reduction under fluoroscopic control [ 28 ]. They also detected relevant intraarticular fragments, which would have remained undetected in conventional fluoroscopy [ 28 ]. Also, other authors have confirmed the benefit of intraoperative 3D imaging [ 29 , 30 ].…”
Section: Intraoperative 3d-imagingmentioning
confidence: 99%
“…For example, after flipping back the osteotomized tibial condyle, it is challenging to exactly double check on the final reduction result centrally. An intraoperative 3D scan or fracturoscopy is required in such a situation to be sure [5,[25][26][27]. Secondly, the extended lateral approach as decribed in this paper, especially if carried out in prone positioning, allows direct access to the posterior-lateral corner from posteriorly.…”
Section: Discussionmentioning
confidence: 99%
“…The arrow and numbers 1 and 2 show once again the depression and the two main fragments corresponding to the markings on a; c Intraoperative coronar 3D scan after allograft implantation and first preliminary reduction attempt secured with wires, below a lateral fluoroscopic image which shows the double plate placement; d Final intraoperative 3D scan after allograft implantation and finalized ORIF the cases after a median follow-up of 8.3 (IQR 4.3 range 3-14.5) months. None of the ten cases required a postoperative revision surgery.The clinical Rasmussen-Score had a median value of 25 (IQR 2.8, range[21][22][23][24][25][26][27][28][29]. Two patients (20%) had excellent (with score > 27) and the eight (80%) had good (score 20-26) clinical results.…”
mentioning
confidence: 99%
“…They can be an essential help in complex anatomic regions and joint fractures. 94 Intraoperative 3D image acquisition can also be obtained through the use of a fixed or mobile fan-beam-CT. They ensure a high image quality, but lack the possibility of intraoperative fluoroscopy.…”
Section: Principal Technologies To Meet Needsmentioning
confidence: 99%